A Global Survey of COVID-19 Vaccine Acceptance Among Healthcare Workers - Noushad, Mohammed (2022)
Objectives: Even though several effective vaccines are available to combat the COVID-19 pandemic, wide disparities in vaccine distribution, and vaccine acceptance rates between high- and low-income countries appear to be major threats toward achieving population immunity. Our global descriptive study aims to inform policymakers on factors affecting COVID-19 vaccine acceptance among healthcare workers (HCWs) in 12 countries, based on income index. We also looked for possible predictors of vaccine acceptance among the study sample. Methods: A structured questionnaire prepared after consultation with experts in the field and guided by the “Report of the SAGE working group on vaccine hesitancy” was administered among 2,953 HCWs. Upon obtaining informed consent, apart from demographic information, we collected information on trust in vaccines and health authorities, and agreement to accept a COVID-19 vaccine. Results: Although 69% of the participants agreed to accept a vaccine, there was high heterogeneity in agreement between HCWs in low and lower-middle income countries (L-LMICs) and upper-middle- and high-income countries (UM-HICs), with acceptance rates of 62 and 75%, respectively. Potential predictors of vaccine acceptance included being male, 50 years of age or older, resident of an UM-HIC, updating self about COVID-19 vaccines, greater disease severity perception, greater anxiety of contracting COVID-19 and concern about side effects of vaccines. Conclusions: COVID-19 vaccine acceptance among HCWs in L-LMICs was considerably low as compared to those from UM-HICs. The lowest vaccine acceptance rates were among HCWs from the African continent. This underlines the need for the implementation of country-specific vaccine promotion strategies, with special focus on increasing vaccine supply in L-LMICs.